Mechanical properties and microstructure analysis of laser surface melting of EN32B low carbon steel. (1st January 2013) - Sivanandham, N.; Rajadurai, A.; Shariff, S.M.; Senthilselvan, J.; Mahalingam, A.
This work presents the findings of laser surface melting (LSM) on microstructure and mechanical properties on the surface layer of the EN32B steel carried out using a high power diode laser (HPDL). The laser treated specimens were characterised by high resolution scanning electron microscopy (HRSEM) and X-ray diffractometer (XRD) for phase analysis. The hardness profile of the laser treated cross-sectional layer was determined by using Vickers hardness tester. It was found that the micro hardness improved to as high value of 405 HV from a value of 160 HV of the substrate material. The wear resistance of the laser surface melted EN32B steel was also found to be increased. The low carbon steel laser surface melted by the HPDL has created lath martensite microstructure. XRD phase analysis confirms the formation of martensite, Fe-Mn-C and iron carbide phases at near surface regions of laser treated samples. Salt spray corrosion testing and potentiodynamic electrochemical corrosion method reveal improved corrosion resistance in the laser treated layers. The hardness value is found to increase from 160 HV to 405 and wear resistance also increases 5–6 times upon laser surface treatment. Corrosion resistance increases tremendously from a period of 7 hours to 49 hours.